Generation of photoionized plasmas in the laboratory of relevance to accretion-powered x-ray sources using keV line radiation - Riley,D; Singh,RL; White,S; Charlwood,M; Bailie,D; Hyland,C; Audet,T; Sarri,G; Kettle,B; Gribakin,G; Rose,SJ; Hill,EG; et al. (High Energy Density Physics, 2024)
We describe laboratory experiments to generate x-ray photoionized plasmas of relevance to accretion-powered xray sources such as neutron star binaries and quasars, with significant improvements over previous work. A keyquantity is referenced, namely the photoionization parameter, defined as ξ = 4πF/ne where F is the x-ray flux andne the electron density. This is normally meaningful in an astrophysical steady-state context, but is alsocommonly used in the literature as a figure of merit for laboratory experiments that are, of necessity, timedependent. We demonstrate emission-weighted values of ξ > 50 erg-cm s− 1 using laser-plasma x-ray sources,with higher results at the centre of the plasma which are in the regime of interest for several astrophysicalscenarios. Comparisons of laboratory experiments with astrophysical codes are always limited, principally by themany orders of magnitude differences in time and spatial scales, but also other plasma parameters. Howeveruseful checks on performance can often be made for a limited range of parameters. For example, we show thatour use of a keV line source, rather than the quasi-blackbody radiation fields normally employed in such experiments, has allowed the generation of the ratio of inner-shell to outer-shell photoionization expected from ablackbody source with ~keV spectral temperature. We compare calculations from our in-house plasma modellingcode with those from Cloudy and find moderately good agreement for the time evolution of both electrontemperature and average ionisation. However, a comparison of code predictions for a K-β argon X-ray spectrumwith experimental data reveals that our Cloudy simulation overestimates the intensities of more highly ionisedargon species. This is not totally surprising as the Cloudy model was generated for a single set of plasma conditions, while the experimental data are spatially integrated.